PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL KOOPERATIF TIPE STAD DI KELAS IV SDN 20 BINUANG KAMPUNG DALAM KOTA PADANG - Alya Nazwa Minisa; Serly Safitri; Hamimah; Ummiatul Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of fourth-grade students at SDN 20 Binuang Kampung Dalam, Padang City, which were caused by limited student participation in the learning process, the use of less effective learning models, and teaching modules that had not fully complied with the requirements of the Merdeka Curriculum based on the deep learning approach. This study aimed to improve students' learning outcomes in Science and Social Studies (IPAS) through the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model.This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The study was conducted in two cycles consisting of planning, implementation, observation, and reflection. Data were collected through test and non-test techniques and analyzed based on the assessment of teaching modules, the implementation of the learning process, and students' learning outcomes. The research subjects were the teacher and fourth-grade students of SDN 20 Binuang Kampung Dalam, Padang City.The results showed continuous improvement in every cycle. The teaching module assessment increased from 87.5% to 95.83% and reached 100%. Teacher activity improved from 89.28% to 92.85% and reached 100%, while student activity increased from 82.14% to 89.28% and reached 96.43%. Students' average learning outcomes increased from 73.25 to 81.91 and reached 89.53 in Cycle II, with a learning mastery rate of 100%. Therefore, the implementation of the STAD cooperative learning model successfully improved the learning outcomes of fourth-grade students in IPAS at SDN 20 Binuang Kampung Dalam, Padang City.